THE RELATIONSHIP BETWEEN EXPOSURE TO HOAX CONTENT AND LITERACY LEVEL ON SOCIAL MEDIA TOWARDS THE CRITICAL ATTITUDE OF GENERATION Z TOWARDS ONLINE NEWS - Ainiyah Rahman Hasibuan; Martha Tri Lestari (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Social media offers many benefits in people's lives including ease of communication, ease of getting information from social media and ease of sending and receiving messages in the form of documents or videos and photos via social media. However, people often receive negative impacts from social media, one of which is receiving hoax information. This study aims to analyze the relationship between exposure to hoax content and the level of social media literacy towards Generation Z in responding to online news. This type of research uses a positivistic quantitative method by distributing questionnaires to 400 respondents to the Z generation community in the city of Bandung. The author uses the Audience Reception theory by Stuart Hall which explains how messages are conveyed by the media produced by encoding and received by decoding by the audience. The results of the study showed that there was a significant relationship between exposure to hoax content and critical attitudes of generation Z. The higher the exposure to hoax content, the lower the critical attitude shown by respondents. In the sense that the more often someone is exposed to false information without being able to verify its truth, the more vulnerable they are to receiving information passively and uncritically.